The apolipoprotein A‐I mimetic peptide, D‐4F, restrains neointimal formation through heme oxygenase‐1 up‐regulation. Issue 12 (2nd August 2017) - Liu, Donghui; Wu, Mengzhang; Du, Qian; Ding, Zhenzhen; Qian, Mingming; Tong, Zijia; Xu, Wenqi; Zhang, Le; Chang, He; Wang, Yan; Huang, Caihua; Lin, Donghai
Abstract: D‐4F, an apolipoprotein A‐I (apoA‐I) mimetic peptide, possesses distinctly anti‐atherogenic effects. However, the biological functions and mechanisms of D‐4F on the hyperplasia of vascular smooth muscle cells (VSMCs) remain unclear. This study aimed to determine its roles in the proliferation and migration of VSMCs. In vitro, D‐4F inhibited VSMC proliferation and migration induced by ox‐LDL in a dose‐dependent manner. D‐4F up‐regulated heme oxygenase‐1 (HO‐1) expression in VSMCs, and the PI3K/Akt/AMP‐activated protein kinase (AMPK) pathway was involved in these processes. HO‐1 down‐regulation with siRNA or inhibition with zinc protoporphyrin (Znpp) impaired the protective effects of D‐4F on the oxidative stress and the proliferation and migration of VSMCs. Moreover, down‐regulation of ATP‐binding cassette transporter A1 (ABCA1) abolished the activation of Akt and AMPK, the up‐regulation of HO‐1 and the anti‐oxidative effects of D‐4F. In vivo, D‐4F restrained neointimal formation and oxidative stress of carotid arteries in balloon‐injured Sprague Dawley rats. And inhibition of HO‐1 with Znpp decreased the inhibitory effects of D‐4F on neointimal formation and ROS production in arteries. In conclusion, D‐4F inhibited VSMC proliferation and migration in vitro and neointimal formation in vivo through HO‐1 up‐regulation, which provided a novel prophylactic and therapeutic strategy for anti‐restenosis of arteries.